Decentralisation of Educational Management: Evidence from Ghanaian Basic Schools - Kyeremeh, Alex; Kor, Jacob Aaworb-nang Maabobr (Advances in Social Sciences Research Journal, 2022)
Although touted as having impacts on educational outcomes in some countries not much attention has been given to evaluating the operations of the District Oversight Committees toward implementing decentralised education management functions at the basic level of education, on a national level. The study sought to evaluate the role of DOECs toward decentralization of school management at the basic level of Education and also identify existing challenges towards their operations. A mixed design was employed in this study. A multistage random sampling technique was used to select 408 public and private schools from 9 regions and interviews conducted with selected District directors and Headteachers from which schools are selected. It was found that the District Education Oversight Committees were sometimes involved in their roles toward Personnel management, Organization of Instruction, and in Planning and Structures. While it was found that DOECs were particularly active in supervision and monitoring in schools they were less active in some personnel management functions as the power and means to perform such functions remained centralised. Key challenges which affected the operations on the DEOCs were financial constraints, inadequate logistics for the operations, inadequacy and delay in supply of teaching and learning materials, delays in decisions on appointments, promotions and sanctions, political interferences, poor communication, and difficulty in monitoring and supervision of school. It was recommended that there a more improved form of devolution may be needed to address some lingering challenges observed after decade of practicing educational decentralization. Again, there should be a consistent supervision of school instructions at various levels of decentralization of educational management to ensure standard is maintained.